2015
DOI: 10.1186/s12885-015-1475-7
|View full text |Cite
|
Sign up to set email alerts
|

Cohort profile: cholangiocarcinoma screening and care program (CASCAP)

Abstract: BackgroundCholangiocarcinoma (CCA) is an extremely aggressive cancer that is usually fatal. Although globally morbidity and mortality are increasing, knowledge of the disease remains limited. The Mekong region of Southeast Asia, and particularly the northeast of Thailand, has by far the highest incidence of CCA worldwide with 135.4 per 100,000 among males and 43.0 per 100,000 among females being reported in Khon Kaen Province. Most patients are first seen during late stage disease with 5-year survival being le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(113 citation statements)
references
References 28 publications
2
94
0
9
Order By: Relevance
“…The aim of this study is to systematically improve the diagnosis and treatment of CCA patients throughout the northeast of Thailand [70]. For the screening cohort, annual ultrasound examination and - as appropriate - biopsy will be provided in order to establish diagnosis as early as possible.…”
Section: Prevention Surveillance and Perspectivesmentioning
confidence: 99%
“…The aim of this study is to systematically improve the diagnosis and treatment of CCA patients throughout the northeast of Thailand [70]. For the screening cohort, annual ultrasound examination and - as appropriate - biopsy will be provided in order to establish diagnosis as early as possible.…”
Section: Prevention Surveillance and Perspectivesmentioning
confidence: 99%
“…Current 5-year survival rates for CCA after surgery and chemotherapy remain poor [<20%, (4)], and clinical trials evaluating targeted therapies in unselected CCA populations have shown minimal benefits (5). Existing CCA classification systems are primarily based on either anatomical location (intrahepatic, perihilar, and distal) or pathological features (cirrhosis, viral hepatitis, and primary sclerosing cholangitis), which do not provide insights into mechanisms of CCA tumorigenesis, nor potential targets for therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 10% of opisthorchiasis patients are likely to develop CCA [4]. Nowadays, although the incidence of opisthorchiasis is declining due to a multi-faceted control program [2], the incidence of CCA in endemic areas of liver fluke, such as in Khon Kaen Province, remains high [5] and the incidence of CCA elsewhere is increasing [6]. This suggests the etiology of HBD and CCA are associated with multifactorial risk factors [7].…”
Section: Introductionmentioning
confidence: 99%